Guiding principles for evaluating the impacts of conservation interventions on human well-being - Woodhouse, Emily (Philos Trans R Soc Lond B Biol Sci, 2015)
Measures of socio-economic impacts of conservation interventions have largely been restricted to externally defined indicators focused on income, which do not reflect people's priorities. Using a holistic, locally grounded conceptualization of human well-being instead provides a way to understand the multi-faceted impacts of conservation on aspects of people's lives that they value. Conservationists are engaging with well-being for both pragmatic and ethical reasons, yet current guidance on how to operationalize the concept is limited. We present nine guiding principles based around a well-being framework incorporating material, relational and subjective components, and focused on gaining knowledge needed for decision-making. The principles relate to four key components of an impact evaluation: (i) defining well-being indicators, giving primacy to the perceptions of those most impacted by interventions through qualitative research, and considering subjective well-being, which can affect engagement with conservation; (ii) attributing impacts to interventions through quasi-experimental designs, or alternative methods such as theory-based, case study and participatory approaches, depending on the setting and evidence required; (iii) understanding the processes of change including evidence of causal linkages, and consideration of trajectories of change and institutional processes; and (iv) data collection with methods selected and applied with sensitivity to research context, consideration of heterogeneity of impacts along relevant societal divisions, and conducted by evaluators with local expertise and independence from the intervention.